The impact of legislative amendments on the effectiveness of alternatives in the EIA in Poland - Chochoł, Adrian (The Opole Studies in Administration and Law, 2025)
The article analyses the impact of the 2019 and 2023 amendments to the Act on Access to Information on the Environment and its Protection, Public Participation in Environmental Protection, and Environmental Impact Assessments (EIA Act) on the functioning and effectiveness of alternatives analysis in the Environmental Impact Assessment (EIA) procedure. The author posits that these modifications have negatively affected the ability of alternatives analysis to provide substantive analyses supporting selection of the optimal variant in the decision-making process regarding environmental decisions. The main research question concerns the way in which these legislative changes have influenced the functioning and effectiveness of this tool. Additionally, the author conducted a detailed analysis of the legislative process to determine the reasons behind the changes. The discussed issue aligns with the current global research focus on streamlining the EIA procedures, especially in the context of the ongoing energy transition and ensuring appropriate mechanisms for public participation. The research employed the dogmatic-legal method, supplemented by the author’s observations from direct involvement in EIA procedures in Poland and experiences from the legislative process of the amendments. The analysis revealed that changes to Article 81(1) of the EIA Act significantly limited the authority’s competence to select an alternative project variant, making it dependent on demonstrating the impossibility of implementing the investment in the variant proposed by the investor. Meanwhile, the amendment to Article 66(1)(5 of the EIA Act reduced the minimum number of alternatives that must be analysed in the EIA report from three to two, depriving the authority of the ability to use a “comparative grid” to reliably assess different options for achieving the investment goal and prevent the development of apparent alternatives. The current regulations significantly limit the possibility of determining optimal environmental conditions, which may contribute to an escalation of social conflicts rather than their minimization.